Handling and fixation of permanent magnets - Tremel, Jan; Hofmann, Benjamin; Risch, Florian (Advanced Materials Research, 2013)
Due to rapid developments within the family of rare-earth materials innovative electrical machines can nowadays be used as high efficient generators in various power, as well as rugged constructed machines for automobile battery based propulsion in hybrid and full electric vehicles. The production of different possible motor concepts spread into different design and creates complex variations especially for the rotor part. Deriving from various research projects, the handling of the permanent magnet components is investigated, including the development of new assembly and fixation methods. © (2013) Trans Tech Publications, Switzerland.
CRIS-Team Scopus Importer:2024-08-06
Keywords: Assembly; Fixation; Handling